2021
DOI: 10.1080/19490976.2021.1902717
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium dentium-derived y-glutamylcysteine suppresses ER-mediated goblet cell stress and reduces TNBS-driven colonic inflammation

Abstract: Endoplasmic reticulum (ER) stress compromises the secretion of MUC2 from goblet cells and has been linked with inflammatory bowel disease (IBD). Although Bifidobacterium can beneficially modulate mucin production, little work has been done investigating the effects of Bifidobacterium on goblet cell ER stress. We hypothesized that secreted factors from Bifidobacterium dentium downregulate ER stress genes and modulates the unfolded protein response (UPR) to promote MUC2 secretion. We identified by mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 127 publications
(180 reference statements)
3
31
0
Order By: Relevance
“… 34 GSH is directly or indirectly synthesized by intestinal bacteria or the liver itself. 33 , 68–70 The present study found that BA administration in mice decreased the hepatic GSSG/GSH ratio. GSH also significantly inhibited CD95 expression and alleviated ConA-induced liver injury in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“… 34 GSH is directly or indirectly synthesized by intestinal bacteria or the liver itself. 33 , 68–70 The present study found that BA administration in mice decreased the hepatic GSSG/GSH ratio. GSH also significantly inhibited CD95 expression and alleviated ConA-induced liver injury in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 62%
“… 32 Some precursor metabolites from intestinal bacteria may affect glutathione (GSH) levels. 33 GSH administration attenuates CD95-mediated hepatic apoptosis and injury in mice. 34 The metabolites, and the intestinal bacteria that produce them, play a vital role in the “liver-gut interaction” and need to be further explored.…”
Section: Introductionmentioning
confidence: 96%
“…In IBD mediated by pathogenic bacteria, they have been proven to regulate the tight junction of Caco-2 cells [ 123 ], counteract Adherent-Invasive Escherichia coli virulence in CD patients, and reduce the secretion of cytokines related to the IL-23/Th17 axis in UC patients [ 124 ]. Furthermore, secreted factors from Bifidobacterium dentium can also down-regulate the endoplasmic reticulum stress gene and regulate the unfolded protein response to promote MUC2 secretion [ 125 ].…”
Section: Native Probiotics and Diseasesmentioning
confidence: 99%
“…bile acids/salts, amino acids and biogenic amines, short-chain fatty acids, and neurotransmitters) in a number of in vitro and in vivo models. Metabolomics measurements can be made on growth media collected from in vitro or ex vivo culture systems used to grow microbes or intestinal organoids ( Engevik et al., 2021a , 2021b , 2021c ; Horvath et al., 2020 ; Ihekweazu et al., 2021 ; Luck et al., 2021 ). There is an increasing number of protocols for metabolomics using extracts of cecal content and fecal samples, and homogenized gastrointestinal tract and brain tissues harvested from gnotobiotic mice ( Engevik et al., 2021a , 2021b , 2021c ; Horvath et al., 2020 ; Ihekweazu et al., 2021 ; Luck et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%